Oral lichenoid lesions: Clinico-pathological mimicry and its diagnostic implications - Santhosh Kumar S Hiremath; Alka D Kale; Seema Charantimath (Wolters Kluwer Medknow Publications, 2011)
Oral cavity is commonly affected by number of lichenoid lesions, whose clinical and histopathologic features overlap due to the presence of inflammatory cells in connective tissue. Segregation of these lichenoid lesions is mandatory as each may embody a distinct disease entity in terms of cause, diagnosis and prognosis. The literature discussed in the article is an attempt to segregate individual lichenoid lesions by defining clinical and histopathologic variations among each other, which avoids the diagnostic problem.